PENINGKATAN PEMAHAMAN PHBS PADA SISWA SDN 010 MELALUI PENYULUHAN KESEHATAN REPRODUKSI (PITIMAS: Journal of Community Engagement in Health, 2025)
Background: Adolescent reproductive health is increasingly becoming a major concern in education and public health. Especially in elementary school environment, where there is not enough information about clean and healthy lifestyle, it may affect their health in the future. Objective: To improve the understanding of students at SDN 010 Batam on the importance of reproductive health care through interactive counseling. Method: counseling that involves interaction, group discussion, and appropriate educational materials, materials include knowledge about the structure of body organs both inside and outside, growth, hygiene, and reproduction, as well as daily healthy lifestyle. Results: increased student understanding of hygiene and healthy living and its effect on reproductive health. Students showed a high level of enthusiasm and the ability to use the knowledge gained in daily life. These findings demonstrate the urgency of the need for structured and continuous reproductive health education in educational settings. Similarly, the community service program has been successful in raising awareness and shaping a continuous healthy lifestyle among adolescents. Conclusion: this step is very important in shaping a healthy generation that cares about reproductive health issues.